2014
DOI: 10.1007/s00414-014-1059-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial communities associated with human decomposition and their potential use as postmortem clocks

Abstract: Most forensic research that is used to better understand how to estimate the postmortem interval (PMI) entails the study of the physiochemical characteristics of decomposition and the effects that environmental factors have on the decomposition process. Forensic entomology exploits the life cycles of arthropods like Diptera (blow flies or flesh flies) and Coleoptera (beetles) deposited on the decaying carcass to determine PMI. Forensic taphonomy, from the Greek word taphos meaning burial, studies the creation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 66 publications
4
60
0
2
Order By: Relevance
“…Our results are also consistent with those of previous studies that have shown a rapid disappearance of aerobic microbial communities during the bloat stage (Finley et al 2015; Goff 2009; Hyde et al 2013; Pascual et al 2017). Abundance patterns of OTUs from Moraxellaceae, all of which are known to be aerobic (Pascual et al 2017), exemplify this pattern: they represent 30.3% of total abundance in the fresh stage, 2.4% in the bloat stage (when anaerobic Clostridia and Enterobacteriaceae are dominant), and 0.78% in the active decay stage.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are also consistent with those of previous studies that have shown a rapid disappearance of aerobic microbial communities during the bloat stage (Finley et al 2015; Goff 2009; Hyde et al 2013; Pascual et al 2017). Abundance patterns of OTUs from Moraxellaceae, all of which are known to be aerobic (Pascual et al 2017), exemplify this pattern: they represent 30.3% of total abundance in the fresh stage, 2.4% in the bloat stage (when anaerobic Clostridia and Enterobacteriaceae are dominant), and 0.78% in the active decay stage.…”
Section: Discussionsupporting
confidence: 93%
“…With the exception of Providencia and Myriodes, most of these genera exhibited increased abundance when the carcasses entered into active decay. This increase in macroinvertebrate-associated taxa is consistent with the increases of macroinvertebrate activity that occur during the active decay stage(Finley et al 2015; Matuszewski et al 2010; Payne 1965).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Studies of cadaver decomposition and its interactions with, and effects on, soil ecology have highlighted the potential of forensic ecogenomics as a powerful tool to estimate PMI and identify clandestine graves through changes in microbial communities [14][15][16][20][21][22][23]. Although this tool has potential advantages compared with conventional methods for estimating PMI, most studies have, however, only considered a single carbon source (the cadaver) while dual sources can provide useful information for forensic practitioners to identify and differentiate gravesites in difficult cases such as transit or clandestine scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…From our postnatal development (8, 9) to post-mortem decomposition (10, 11) the human body is thoroughly influenced by, and most times highly dependent on, its associated microbiome and virome (see Table 1). The beneficial effects a stable microbiota (see Table 1) has on host fitness has been extensively reviewed, as these microbes often protect from disease (1214), aid in food digestion (1517), increment nutrient absorption and vitamin production (1821), propel the maturation of host immune systems (2225) and organ development (26), among many other attributes.…”
Section: Potential Pathogens or Ancient Symbionts?mentioning
confidence: 99%